Intercalating Electron Dyes for TEM Visualization of DNA at the Single‐Molecule Level. (7th February 2019) - Kabiri, Yoones; Angelin, Alessandro; Ahmed, Ishtiaq; Mutlu, Hatice; Bauer, Jens; Niemeyer, Christof M.; Zandbergen, Henny; Dekker, Cees
Abstract: Staining compounds containing heavy elements (electron dyes) can facilitate the visualization of DNA and related biomolecules by using TEM. However, research into the synthesis and utilization of alternative electron dyes has been limited. Here, we report the synthesis of a novel DNA intercalator molecule, bis‐acridine uranyl (BAU). NMR spectroscopy and MS confirmed the validity of the synthetic strategy and gel electrophoresis verified the binding of BAU to DNA. For TEM imaging of DNA, two‐dimensional DNA origami nanostructures were used as a robust microscopy test object. By using scanning transmission electron microscopy (STEM) imaging, which is favored over conventional wide‐field TEM for improved contrast, and therefore, quantitative image analysis, it is found that the synthesized BAU intercalator can render DNA visible, even at the single‐molecule scale. For comparison, other staining compounds with a purported affinity towards DNA, such as dichloroplatinum, cisplatin, osmium tetroxide, and uranyl acetate, have been evaluated. The STEM contrast is discussed in terms of the DNA–dye association constants, number of dye molecules bound per base pair, and the electron‐scattering capacity of the metal‐containing ligands. These findings pave the way for the future development of electron dyes with specific DNA‐binding motifs for high‐resolution TEM imaging. Abstract : One by one : Staining compounds containing heavy elements (electron dyes) can facilitate the visualization of DNA and related biomolecules by using scanning transmission electron microscopy (STEM). The design and application of bis‐acridine uranyl, as an intercalating analogue to uranyl acetate, for single‐molecule visualization of DNA is reported.